THE ANALYSIS OF CURRENT STATE AND PROBLEMS OF DEVELOPMENT OF POTENTIAL OF DOMESTIC KNOWLEDGE-INTENSIVE INDUSTRIES (ON THE EXAMPLE OF AIRCRAFT INDUSTRIES) - A. Sazonov; E. Matushina; M. Sazonova (Вестник университета)
Article is devoted to a complex research of opportunities and obstacles of development of capacity of domestic knowledge-intensive branches. As a key branch the aviation industry is chosen. Authors considered a problem of efficiency of the organization and performance of research works in domestic aircraft industry. The results of a research received when carrying out the comparative, horizontal and vertical analysis of effectiveness of the Russian scientific organizations and similar foreign companies are stated. Following the results of a research authors drew a conclusion on prevalence of low stability of financing of aviation science that leads to increase in risk of not achievement of target level of characteristics in the set terms and insufficiency of a scientific and technical reserve.